The role of clopidogrel in the current treatment of acute coronary syndrome - I. S. Yavelov («REMEDIUM GROUP» Ltd., 2020)
In the article, a review is given of the facts that determined contemporary views of the role of clopidogrel in the treatment of acute coronary syndrome. The author described a history of the clinical studies of clopidogrel in acute coronary syndrome (ACS), analysed its role in the current approaches to the treatment of the disease during the widespread use of other platelet P2Y12 receptor antagonists (ticagrelor and prasugrel).The article discusses circumstances, when clopidogrel may have additional advantages, particularly the role of adherence to prolonged double antiplatelet therapy, as well as situations, when sever suppression of platelet function can be decreased (treatment de-escalation). According to a prospective randomized open-label PoPular Age study, clopidogrel combined with acetylsalicylic acid in patients with ACS without persistent ST segment elevations at the age of ≥70 years showed better adherence to treatment over the coming year as compared with clopidogrel combined with ticagrelor or prasugrel. As a result, these two approaches had comparable efficacy. Today, treatment de-escalation is a necessary measure to extend the double antiplatelet therapy in cases, when continued administration of prasugrel or ticagrelor appears unacceptable. There is insufficient evidence for the routine implementation of de-escalation in stented patients with ACS, although a small prospective, one-centre randomized open-label ToPIC study shows that this approach is safe.The author provides a review of the results of recently presented prospective studies on the choice of a platelet P2Y12 receptor antagonist for long-term treatment of acute coronary syndrome, taking into account the residual platelet reactivity and cytochrome p450 2c19 genetic polymorphisms. Among them are multicenter open randomized clinical TRoPICAL-ACS study, multicenter randomized open-label PoPular Genetics and TAILoR PCI studies. According to the study results, the long-term outcomes in stented patients with ACS with a good response to clopidogrel assessed by the residual functional activity of platelets or by studying cytochrome p450 2c19 genetic polymorphisms may not be worse than those during use of prasugrel or ticagrelor.